Good manufacturing practice-grade generation of CD19 and CD123-specific CAR-T cells using piggyBac transposon and allogeneic feeder cells in patients diagnosed with B-cell non-Hodgkin lymphoma and acute myeloid leukemia - Mucha, Martin; Štach, Martin; Kaštánková, Iva; Rychlá, Jana; Vydra, Jan; Lesný, Petr; Otáhal, Pavel (Frontiers in Immunology, 2024)
Background: The non-viral production of CAR-T cells through electroporation of transposon DNA plasmids is an alternative approach to lentiviral/retroviral methods. This method is particularly suitable for early-phase clinical trials involving novel types of CAR-T cells. The primary disadvantage of non-viral methods is the lower production efficiency compared to viral-based methods, which becomes a limiting factor for CAR-T production, especially in chemotherapy-pretreated lymphopenic patients. Methods: We describe a good manufacturing practice (GMP)-compliant protocol for producing CD19 and CD123-specific CAR-T cells based on the electroporation of transposon vectors. The lymphocytes were purified from the blood of patients undergoing chemotherapy for B-NHL or AML and were electroporated with piggyBac transposon encoding CAR19 or CAR123, respectively. Electroporated cells were then polyclonally activated by anti-CD3/CD28 antibodies and a combination of cytokines (IL-4, IL-7, IL-21). The expansion was carried out in the presence of irradiated allogeneic blood-derived mononuclear cells (i.e., the feeder) for up to 21 days. Results: Expansion in the presence of the feeder enhanced CAR-T production yield (4.5-fold in CAR19 and 9.3-fold in CAR123). Detailed flow-cytometric analysis revealed the persistence of early-memory CAR-T cells and a low vector-copy number after production in the presence of the feeder, with no negative impact on the cytotoxicity of feeder-produced CAR19 and CAR123 T cells. Furthermore, large-scale manufacturing of CAR19 carried out under GMP conditions using PBMCs obtained from B-NHL patients (starting number=200x10e6 cells) enabled the production of >50x10e6 CAR19 in 7 out of 8 cases in the presence of the feeder while only in 2 out of 8 cases without the feeder. Conclusions: The described approach enables GMP-compatible production of sufficient numbers of CAR19 and CAR123 T cells for clinical application and provides the basis for non-viral manufacturing of novel experimental CAR-T cells that can be tested in early-phase clinical trials. This manufacturing approach can complement and advance novel experimental immunotherapeutic strategies against human hematologic malignancies.